Students' Needs Survey On Speaking Class Of UIN Satu Tulungagung - Latifatul Isro'iyah; Dwi Ima Herminingsih; Ervian Dinta H; Fathan Rifqi Amanatillah (International Journal of Education, Vocational and Social Science, 2024)
The research is related to the analysis of what the students need when they take the speaking course. The findings can be a useful reference to design the proper teaching materials due to the achievement of teaching goals. The study investigated 1) the difficulties faced by students in mastering speaking, 2) the most helpful speaking activities for improving speaking ability, 3) the topic preferred by students in speaking lesson, 4) the materials needed by students in speaking. Data collection method used the questionnaires distribution. The 32 first-semester students of the English Education Department have participated to response the questionnaire items. Respondents were also interviewed to collect additional information. The research found the difficulties faced by the students using appropriate vocabulary and grammar, expressing ideas and opinions, understanding and responding to questions, pronunciation and intonation maintaining conversation. Role-playing exercises pair conversation, group discussion are the favorite activities in speaking practices. The casual conversations with friends and family seem to be interesting topic for the students. Meanwhile the topics which are familiar with their daily life can be media to prompt their speaking performance. In addition, the speaking areas they like most are giving and replying to compliments, asking people to do things (requesting), offering to do things; thanking people, expressing appreciation & gratitude, replying to thanks, appreciation & gratitude. In the case of linguistic aspects, the students think the pronunciation and intonation practices are very prominent to speak well.